Comparative Study of Major Central Bank’s Monetary Policy in Response to the Pandemic Crisis - Gergana Mihaylova-Borisova (Finance, Accounting and Business Analysis, 2021)
Objective: The study aims to investigate the policy, performed by the main central banks during the crisis, related to spread of the COVID-19 crisis all over the world. The Central bank’s policy was one of the key policies for the countries to counter the negative effects, from the coming new crisis. The crisis is different in character from the previous global crisis in 2009 and it is characterized with higher negative impacts on the economic activity and unemployment of the countries. Methodology:The study examines the monetary policy tools used by the major central banks in particular the FR (Federal Reserve), the European central bank, the BoE (Bank of England) during the COVID-19 crisis. The data used are the official one, published by the Eurostat, European central bank, Federal Reserve, OECD. Through the methods of analysis and synthesis the effectiveness of the monetary policy, done by thecovered central banks, is investigated. The data used are for the period 2007-2021.Results: The analyses indicatethat theBank of England, as well as the FR was in more privileged terms than the European central bank (ECB) before the COVID-19 crisis. Their main interest rates were positive and these banks could apply conventional instruments of policy at the beginning of the crisis before conducting the nonconventional policy tools.Implication: The study’s results are beneficial for central banks for countering the negative effects of the COVID-19 crisis, turning to the deep economic crisis afterward.